PEMROGRAMAN SLOPE MINIMUM DAN KONSENTRASI SEDIMEN MAKSIMUM SEBAGAI ALTERNATIF PENDIMENSIAN SALURAN - Setiyadi Setiyadi (UKI Press, 2020)
ABSTRACT Design of dimension channel can use Minimum Slope and Maximum Concentration Sediment method. Minimum Slope is slope of channel, where is condition it the energy of flow is minimum, so channel condition is stabile. Maximum Sediment Concentration is method of sediment transport capacity, resistant and optimum it. Two methods are to produce of the same dimension of channel.